2015
DOI: 10.1111/ced.12734
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory function for miR-29a in keloid fibrogenesis

Abstract: These findings show that miR-29a exerts as a novel regulator in the fibrogenesis of keloid, suggesting that miR-29a might be a novel marker for keloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…87 Recently, miR-29a, another miRNA with decreased expression in keloid fibroblasts, was also shown to negatively regulate type I/III collagen expression. 88 Further miRNAs involved in pathological scar formation include miR-21, which promotes fibroblast proliferation in HTS formation and in keloids; miR-200b and miR-199a-5p, which inhibit fibroblast proliferation; and miR-10a and -181c, which regulate collagen I generation (Table 3). 89–95 …”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…87 Recently, miR-29a, another miRNA with decreased expression in keloid fibroblasts, was also shown to negatively regulate type I/III collagen expression. 88 Further miRNAs involved in pathological scar formation include miR-21, which promotes fibroblast proliferation in HTS formation and in keloids; miR-200b and miR-199a-5p, which inhibit fibroblast proliferation; and miR-10a and -181c, which regulate collagen I generation (Table 3). 89–95 …”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…Keloids generally occur following an abnormal wound healing; however, the pathogenesis remains unclear (61). Zhang et al (62) determined that all miR-29 family members are expressed in keloid fibroblasts (KFs) and fresh skin biopsy specimens (obtained 24-48 h after surgery) and, in particular, miR-29a is highly expressed in KFs. The authors also evaluated the interaction of miR-29a and collagen type III α1 chain (COL3α1) and demonstrated that miR-29a directly regulates enhancement of collagen production.…”
Section: Keloidsmentioning
confidence: 99%
“…The authors also evaluated the interaction of miR-29a and collagen type III α1 chain (COL3α1) and demonstrated that miR-29a directly regulates enhancement of collagen production. Furthermore, in normal fibroblasts, miR-29a directly regulates collagen production via affecting TGF-β expression (62). In another study, Liu et al (63) used microarray analysis for comparative miRNA profiling between keloid tissue and normal skin tissue samples.…”
Section: Keloidsmentioning
confidence: 99%
“…MiRNAs partly suppress the expression of target genes through binding to their 3′ untranslated regions (UTR) and consequently influence a variety of physiological and pathological processes, including proliferation, metabolism, apoptosis, and invasion [4][5][6]. Emerging evidence has shown that miRNAs contribute to hypertrophic scarring or keloid formation [7][8][9]. Earlier, Zhang et al [7] reported that miR-29a directly regulates the translation of various ECM mRNAs, such as the collagen superfamily, in fibrogenesis of keloids, suggesting utility as a novel marker for keloid.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that miRNAs contribute to hypertrophic scarring or keloid formation [7][8][9]. Earlier, Zhang et al [7] reported that miR-29a directly regulates the translation of various ECM mRNAs, such as the collagen superfamily, in fibrogenesis of keloids, suggesting utility as a novel marker for keloid. Downregulation of miR-125b in psoriatic skin has been shown to contribute to keratinocyte hyperproliferation [8].…”
Section: Introductionmentioning
confidence: 99%